EVALUATIONOFUNEMPLOYMENTPROBLEMSININDIAWITH SPECIAL FOCUS TO CONSEQUENCES AND REMEDIES (International Journal of Food and Nutritional Sciences, 2023)
The greatest threat now facing India is unemployment. Both educated and industrial employees have been impacted by unemployment in metropolitan areas. The main issue in India right now is structural unemployment, which can manifest in both overt and covert ways. Every person needs to work in the economy to sustain their daily needs. A person is considered unemployed if they actively seek employment but are unsuccessful in doing so. The level of unemploymentisagoodindicatoroftheeconomy'shealth.Theunemployment rateiscalculatedasthetotalnumberofunemployedpeopledividedbythetotallabourforce. Themobilizationofresources,acceleratedgrowth,selectivepatternofinvestment,prudent choice of techniques, an appropriate spectrum of economic activities in rural and urban areas, and theaccessibility of complementary factors of production allpoint tothe need for a multifaceted approach to the problem.